Health Literacy Levels Among Adult Support Group Members and the General Adult Public : A Focus Group Approach - Daniel Czech; June Alberto; A. Joyner (Georgia Southern University, 2007)
Health literacy has been identified as lacking in 47% of Americans (The National Academies, 2004). While health literacy reports of studies conducted in the southern section of the United States are available (DeWalt et al., 2004; Kennen et al. 2005), this research team found limited research that provides health literacy levels of the southeast, rural Georgia population. The purpose of this exploratory study was to examine and compare health literacy of health-related support group members and non group members in southeast Georgia utilizing a focus group methodology developed by Kreuger (1994). After Institutional Review Board approval at a local university, the research team utilized 5-10 established Health-related Support Groups of 6-10 individuals in the southeastern part of the United States. An additional four focus groups composed of persons not associated with a health-related support group were also used for comparative purposes. Participants were recruited with the assistance of local health care providers. The initial open-ended questions consisted of items such as: "Describe your experience reading health resources." "What makes a health resource difficult to read, as well as easy to read?" The moderator utilized additional probing questions and reframing comments as necessary (Kreuger, 1994). The data were analyzed by the qualitative content analysis method described by Berg (1989). The themes that emerged across groups reflected confusion about medication directions, health terms, and communication from health care providers and doubt about the integrity of and inability to read the small print of health information. Prevention and faith in God were identified as important to self-care. Rationales for themes and future research ideas are discussed.